Pancreatic islets engineered with a FasL protein induce systemic tolerance at the induction phase that evolves into long‐term graft‐localized immune privilege. Issue 5 (5th January 2020) - Woodward, Kyle B.; Zhao, Hong; Shrestha, Pradeep; Batra, Lalit; Tan, Min; Grimany‐Nuno, Orlando; Bandura‐Morgan, Laura; Askenasy, Nadir; Shirwan, Haval; Yolcu, Esma S.
Abstract : We have previously shown that pancreatic islets engineered to transiently display a modified form of FasL protein (SA‐FasL) on their surface survive indefinitely in allogeneic recipients without a need for chronic immunosuppression. Mechanisms that confer long‐term protection to allograft are yet to be elucidated. We herein demonstrated that immune protection evolves in two distinct phases; induction and maintenance. SA‐FasL‐engineered allogeneic islets survived indefinitely and conferred protection to a second set of donor‐matched, but not third‐party, unmanipulated islet grafts simultaneously transplanted under the contralateral kidney capsule. Protection at the induction phase involved a reduction in the frequency of proliferating alloreactive T cells in the graft‐draining lymph nodes, and required phagocytes and TGF‐β. At the maintenance phase, immune protection evolved into graft site‐restricted immune privilege as the destruction of long‐surviving SA‐FasL‐islet grafts by streptozotocin followed by the transplantation of a second set of unmanipulated islet grafts into the same site from the donor, but not third party, resulted in indefinite survival. The induced immune privilege required both CD4 + CD25 + Foxp3 + Treg cells and persistent presence of donor antigens. Engineering cell and tissue surfaces with SA‐FasL protein provides a practical, efficient, and safe means of localized immunomodulation with important implications for autoimmunity and transplantation. Abstract : Pancreatic islet grafts modified to transiently display a novel form of FasL protein on surface initiate a cascade of immunoregulatory mechanisms, involving apoptosis of alloreactive T cells, production of TGFb, and generation of Treg cells, that establish a bimodal tolerance, systemic at the induction phase and localized to the graft site at the maintenance phase.